HIV testing campaigns and treatment interventions for control of epidemic HIV growth among heterosexuals: a mathematical modelling study. (October 2016) - Wong, Ngai Sze; Wong, Ka Hing; Tsang, Owen T Y; Lee, Man Po; Lee, Shui Shan
Abstract: Background: In 2015, WHO recommended universal antiretroviral treatment for HIV irrespective of CD4 cell count. The impact of this recommendation on heterosexual HIV transmission, especially in low prevalence countries, has not been well-characterised. In Hong Kong, 38% of reported HIV cases are heterosexually acquired. We aimed to model the impacts of enhanced HIV testing and immediate treatment to provide a reference to other provinces in China. Methods: We developed deterministic compartmental models (sexually active heterosexual males and females) for simulation of HIV epidemiology for 1983–2011 in Hong Kong, with data projected to 2012–20. Model parameters were derived from the literature and longitudinal clinical data from 2174 heterosexual adults who were diagnosed in 1984–2014. HIV surveillance data were retrieved from annual surveillance reports to validate projection results. The model was structured by HIV disease stages and cascade of HIV care, and in the knowledge that at least 50% of heterosexual males had acquired HIV infections non-locally. The outcome of three interventions (immediate treatment, HIV testing campaigns at 5-year intervals, and testing campaigns with immediate treatment) were examined. Ethics approval was obtained from the Joint Chinese University of Hong Kong–New Territories East Cluster Clinical Research Ethics Committee (CREC), Kowloon West Cluster Research Ethics Committee, and Kowloon East Cluster Research Ethics Committee. Data access approval was granted by Department of Health, Hong Kong Special Administrative Region Government. Findings: Without interventions, the total number of HIV heterosexual prevalent cases (including undiagnosed) was projected to increase from 2804 in 2014 to 3533 by 2020 (difference 26·0% while incidence would increase from 108 new cases in 2014 to 115 in 2020 (difference 6·5%). Compared with these base rates, a testing campaign would lead to a temporary rise in new diagnoses but fewer cases overall (prevalence 3484 by 2020; difference −1·4%; incidence 108 in 2020, difference −6·5%). Immediate treatment provided smaller gains (prevalence 3528 by 2020; difference −0·1%; incidence 112 in 2020, difference −2·6%) while a testing campaign with immediate treatment (prevalence 3474 by 2020; difference −1·7%; incidence 104 in 2020, difference −9·6%) provided small additional gains to the testing campaign. Interpretation: In Hong Kong, an HIV testing campaign could avert more heterosexual infections than immediate treatment alone. Our model can be applied in places where antiretroviral therapy is widely accessible, but adjustment of access to care pattern may be needed in other places with similar epidemiological profiles. Funding: Council for the AIDS Trust Fund.